2023
DOI: 10.3390/vaccines11091425
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Bivalent Booster in Pregnancy: Maternal and Neonatal Antibody Response to Omicron BA.5, BQ.1, BF.7 and XBB.1.5 SARS-CoV-2

Wei-Chun Chen,
Shu-Yu Hu,
Ching-Fen Shen
et al.

Abstract: Our study was to investigate the effects of bivalent COVID-19 booster vaccination during pregnancy on neutralizing antibody (Nab) levels in maternal blood (MB), transplacental transmission in umbilical cord blood (CB), and efficacy against Omicron SARS-CoV-2 subvariants including BA.5, BF.7, BQ.1, and XBB.1.5. We collected MB and CB from 11 pregnant participants during baby delivery and detected Nab inhibition by enzyme-linked immunosorbent assays (ELISA). Nab inhibition was 89–94% in MB and 82–89% in CB for O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Antibodies elicited by BNT162b2 and mRNA-1273 original vaccines are found in infant cord blood and the breast milk of vaccinated people, demonstrating that mRNA vaccines elicit a substantial antigen-specific immune response in the parent that is efficiently transferred to the fetus or newborn [ 166 ]. The bivalent variant-adapted vaccines have been shown to elicit robust neutralizing antibody responses to recent variants, including BA.5, BQ.1, and XBB.1.5, in maternal blood and umbilical cord blood [ 167 ]. The effectiveness of original COVID-19 mRNA vaccines in pregnant individuals and their infants is well established [ 168 , 169 ].…”
Section: Populations Of Interestmentioning
confidence: 99%
“…Antibodies elicited by BNT162b2 and mRNA-1273 original vaccines are found in infant cord blood and the breast milk of vaccinated people, demonstrating that mRNA vaccines elicit a substantial antigen-specific immune response in the parent that is efficiently transferred to the fetus or newborn [ 166 ]. The bivalent variant-adapted vaccines have been shown to elicit robust neutralizing antibody responses to recent variants, including BA.5, BQ.1, and XBB.1.5, in maternal blood and umbilical cord blood [ 167 ]. The effectiveness of original COVID-19 mRNA vaccines in pregnant individuals and their infants is well established [ 168 , 169 ].…”
Section: Populations Of Interestmentioning
confidence: 99%
“…Research indicates that pregnant women are at increased risk of severe complications such as preeclampsia and preterm births [ 3 ]. Maternal vaccination for COVID-19 not only protects these women but also, through the transfer of neutralizing antibodies across the placenta, offers protection to the fetus against the virus and its variants [ 4 , 5 , 6 ]. This approach emphasizes the critical role of vaccinations in protecting vulnerable populations, marking a substantial advancement in public health and scientific development amid the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In our previously published research, it was observed that COVID-19 vaccination in pregnant women generated neutralizing antibodies that were transmitted to the fetus via transplacental transmission, and these transferred antibodies could function within the fetal system to provide protection against SARS-CoV-2 including various subvariants [ 4 , 5 , 6 ]. This evidence supports the administration of COVID-19 vaccines among pregnant women as a strategic measure to protect both mother and fetus.…”
Section: Introductionmentioning
confidence: 99%
“…This process, which prominently involves the transfer of SARS-CoV-2 neutralizing antibodies (Nabs), promises potential protection for both fetuses and newborns [ 6 , 7 , 8 , 9 ]. Intriguingly, this protective mantle seems to extend its coverage even to emerging SARS-CoV-2 strains, including the Omicron variant [ 10 ]. Our previous research, along with corroborating studies, consistently highlights the criticality of these Nab transfers [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, this protective mantle seems to extend its coverage even to emerging SARS-CoV-2 strains, including the Omicron variant [ 10 ]. Our previous research, along with corroborating studies, consistently highlights the criticality of these Nab transfers [ 8 , 10 , 11 ]. Such defenses furnish newborns with a layer of immunity against pernicious threats like SARS-CoV-2, further endorsing the vaccination of pregnant women [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%